Lasing at 60.8 nm in Ne-like sulfur ions in ablated material excited by a capillary discharge - Tomasel, F. G., author; Shlyaptsev, V. N., author; Rocca, Jorge J., author; Macchietto, C. D., author; American Physical Society, publisher (Colorado State University. Libraries, 1997)
We report the observation of discharge-pumped extreme ultraviolet lasing in collisionally excited ions of a material ablated from a solid target. Excitation of sulfur plasmas by a capillary discharge resulted in amplification of the J=0-1 line of Ne-like sulfur at 60.8 nm, with a gain coefficient of 0.45 cm-1 and a gain-length product of 7.5. Overheating of the electron temperature and transient population effects are computed to make a significant contribution to the measured gain.